Antimony speciation and potential ecological risk of metal(loid)s in plain wetlands in the lower Yangtze River valley, China. (March 2019) - Yao, Cheng; Jiang, Xia; Che, Feifei; Wang, Kun; Zhao, Li
Abstract: Increasing attention is being paid to Sb as a primary hazardous substance, and further systematic studies of Sb behavior in freshwater wetlands are required. The plain wetlands in Lake Taihu basin located in lower Yangtze River valley, are heavily populated and economically developed area in China. The plain wetlands receive polluted water from point sources (textile and printing plants). In this study, Sb speciation in plain wetlands was investigated and the potential ecological risk of 8 metal(loid)s (As, Cd, Cr, Cu, Ni, Pb, Zn, Sb) were assessed. The mean Sb concentration in the wetlands water is 7.03 μg L −1, which consist of pentavalent, trivalent, organic Sb dissolved in water and a great part that attached to suspend solids (SS). Statistical analysis indicated that Sb(Ⅲ) is dissolved from SS and then further oxided to Sb(V) accompanied with tailing water discharged into wetlands; presence of organic Sb is related to microorganic in eutrophic environment; precipitation of SS is the dominant factor for distribution of bioavailable Sb in surficial sediment. The toxicity coefficient factor for Sb is proposed as 10 and ambient background of 8 metal(loid)s are set up. The potential ecological risk for plain wetlands was 135, which was low level. As, Cd and Sb were main contributors to the ecological risks. The wetlands are threatened by Sb pollution, which should be restrict by reducing the concentration of SS and Sb in tailing water from local water treatment facilities. Graphical abstract: Image 10115 Highlights: Sb's toxicity coefficient of 10 was determined and was used to evaluate potential ecological risk of plain wetlands. Sb speciation in water and sediment of plain wetlands were performed. The factors affecting the distribution of Sb species in water were analyzed. The fate of Sb pollutants from textile mill and printing industries plain wetlands was illustrated.